Biliothoracic Fistula after Microwave Ablation of Liver Metastasis : Literature Review. (12th May 2021) - Tassi, Valentina; Mosillo, Claudia; Mutignani, Massimiliano; Cirocchi, Roberto; Ragusa, Mark; Bracarda, Sergio; Passalacqua, Giovanni; Marinozzi, Gabriele; Allegritti, Massimiliano
Abstract : Microwave ablation is a safe and effective interventional approach, widely used in the treatment of unresectable primary or metastatic hepatic lesions. Thoracobiliary fistula is a rare postablation complication that can be treated with a conservative or surgical approach. We reviewed aetiology, pathogenesis, clinical picture, diagnostic possibilities, and therapeutic options for biliothoracic fistula developed after microwave ablation of liver metastasis. Furthermore, we reported our experience of successful conservative management of a nonhealing thoracobiliary fistula occurred after percutaneous thermal ablation of colorectal cancer liver metastasis. Our case supports a conservative approach based on percutaneous biliary system decompression and synthetic glue embolization for the treatment of combined biliopleural and biliobronchial fistula.